(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Street theater is the object of analysis in this work. By this way, with the intention of thinking aboutdramaturgical aspects of scenic occupations in public space, it assumes that the main objective is to make some considerations about street theater as an instrument of reflection. About this, we start observating the show Final da Tarde, by Grupo Teatro de Caretas, pondering relations of this theatrical modality with the city environments. Our theory base is mainly found in the texts “Reflexões sobre o conceito de teatro de rua”, from the André Carreira (Teatro de rua); “Relatos de espaço”, by Michel de Certeau (A invenção do cotidiano); and “Final da Tarde”, by actress Vanéssia Gomes (Cicatriz).